(untitled) (Research, Society and Development, 2020)
Objective: to present the main psychological effects of COVID-19 on nursing professionals, highlighting the main factors that cause psychological stress. Method: This work is an integrative review with a qualitative approach, elaborated from a bibliographic survey, using books and scientific articles. The following databases were accessed: SCIELO, LILACS, MEDLINE, and VHL. Results: nurses, even though they work in the front line to fight the disease, often suffer from the lack of trained collaborators, the injury mark with the use of all PPE’s, coupled with high working hours, as well as the lack of health equipment. individual protection and lack of information on how to use it and lack of staff to assist patients with Conclusion: Therefore, with close contact with patients with COVID-19 in hospital institutions, and the display of patients’ psychological and physical suffering, there is a condition that nurses who are in daily contact are more predisposed to suffer stress due to the psychological problems of the disease, thus requiring the intervention of a multidisciplinary team, so that it is not removed from their activities.